Implementação de tecnologia de produção na pequena propriedade rural: um estudo de caso empreendedor da produção de azeites de oliva e de abacate - Evandro Geraldo de Lima (2023)
The implementation of technologies in small rural properties has been seen as a fundamental factor for decision-making in agribusiness in general and in this case study, in the production of olive oil and avocado. The activity in the small rural property has certain factors that differ from other economic activities, and the producer needs to control, organize and plan his production, that is, to promote efficient management, in order to obtain greater profitability, mitigating risks. It is also important for the producer to continuously dedicate himself to learning, with knowledge updating. Thus, the objective was to analyze how the implementation of production technology in small properties occurs, analyzing possible paths such as opportunities for a more competitive activity, adapting solutions for better management, productivity and economic results, under the management of the rural producer. This analysis addresses the participation of science, the development of partnerships, the diversification of products and services with a focus on the evolution of revenues compatible with the objectives of the activity, in which the implementation of technologies can be used as an important tool to administer and manage small properties. rural areas, as it enables efficient control of agribusiness activities, as well as serving as a source of information for future decision-making. The methodological procedures used in this research were characterized as exploratory and descriptive, employing bibliographic research, documentary research and field research as methods. The qualitative approach was used to respond to the research problem. To support the presentation and discussion of the results, a theoretical basis was sought in subjects such as entrepreneurship, innovation, implementation of production technologies, innovation and technologies used in the extraction of olive and avocado oils. The growing production of olive oil and avocado in rural properties can be observed and compared after the implementation of technologies. This analysis also considered the entrepreneurial posture, the absorption of knowledge, the adequacy of technologies, partnerships, opportunities in the market and the results, based on the evaluation of the facilitators and obstacles that integrate the process of implementing production technologies.